Recherches sur la transitude au Québec: entre absence et exploitation des savoirs trans - Clark Pignedoli; Maxime Faddoul (Genre, Sexualité et Société, 2019)
En suivant l’approche méthodologique de l’autoethnographie, cet article se penche sur la question de l’exploitation des personnes trans en tant que travailleur·se·s précaires de l’université néolibérale. On met en relief la double dynamique d’effacement et d’exploitation des personnes trans « en tant que trans », en soulignant qu’au sein du biocapitalisme, la transitude produit de la valeur qui peut être extraite afin de donner un nouveau souffle aux processus d’accumulation de la richesse. Les conditions de travail des personnes trans dans le domaine de la recherche sont ainsi surdéterminées par ces nouveaux mécanismes d’extractivisme. En guise de conclusion, on partage certaines stratégies de résistance pour renverser cette double dynamique.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; amériques; approches et analyses; biolcapitalisme; canada; capitalisme; cours; discipline; exploitation; premier cycle; périodes historiques; québec; régions géographiques; résistance; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; trans; travail; travail gratuit; travail social; université; violences; études de genres

Neoliberal reform and family engagement in schools: An intersectional gender analysis - Nygreen, Kysa (Policy Futures in Education, 2019)
This article presents an exploration of the work of family engagement in a racially- and linguistically-diverse, high-poverty, urban school district in a state of continuous neoliberal reform. Drawing from qualitative research methods, it is argued that family engagement is being reshaped by the imperatives of educational neoliberalization while, at the same time, remaining out of touch with the needs and concerns of families who are racially stigmatized, linguistically diverse, and experiencing extreme economic insecurity. It is further argued that school personnel charged with family engagement carry out exploited, invisible, and emotional tasks that increase in quantity and intensity as the social safety net declines under neoliberalism. Applying an intersectional gender analysis of emotional labor and the re-privatization of social reproduction offers an illustration of how family engagement in neoliberal schools both exploits and reinforces hierarchies of race–class–gender while obscuring these processes through neoliberal discourses of individual responsibilization. © The Author(s) 2018.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capitalisme; inégalités; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; systèmes d'oppressions; thématiques; travail; travail émotionnel; états-unis

The gendered discourse of work-family balance in the oil and gas industry - Williams, Christine L. (Social Currents, 2018)
U.S. corporations have been slow to adopt family-friendly workplace accommodations, despite decades of research demonstrating their value. Some hope that the millennial generation will spur corporate change because, compared with older generations of workers, young people purportedly strive for more balanced lifestyles and gender equality in their relationships. This study examines the experiences of early career scientists and engineers employed by a major oil and gas corporation that has not implemented family-friendly accommodations, asking whether these highly trained workers seek work-family balance and whether they parlay these desires into requests for accommodation from their employer. Interviews reveal a gendered discourse of work-family balance at this firm: mothers and prospective mothers describe intense work-family conflict, but they blame themselves and not their employer. A number of men, in contrast, express satisfaction with their work-family balance, yet their narratives reveal that their achievement of balance depends on a traditional gender division of labor in the home. Some men and women seek alternative forms of balance that do not involve family; if thwarted from pursuing this goal, they are inclined to exit the company. These discourses of balance reflect neoliberal assumptions, reproduce gender inequality, and suggest the need for an alternative to the voluntary approach to promoting work-family policies. © 2017, © The Southern Sociological Society 2017.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capitalisme; conciliation famille-travail; discipline; famille; industrie pétrolière; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

A voice from the South - Cooper, Anna Julia (University of North Carolina at Chapel Hill Library, 2017)
The first book by Anna J. Cooper, A Voice From the South, presents strong ideals supporting racial and gender equality as well as economic progress. It’s a forward-thinking narrative that highlights many disparities hindering the African American community. Anna J. Cooper was an accomplished educator who used her influence to encourage and elevate African Americans. With A Voice From the South, she delivers a poignant analysis of the country’s affairs as they relate to Black people, specifically Black women. She stresses the importance of education, which she sees as a great equalizer. Cooper considers it a necessary investment in not only the individual but the community. She also criticizes the depictions of African Americans in literature by some of the day’s most popular authors. She calls for more realistic portrayals that are both honest yet positive. Cooper provides an unflinching critique of mainstream America as it relates to the Black population. A Voice From the South broaches pivotal topics such as women’s rights, segregation and the need for higher education. With an eye-catching new cover, and professionally typeset manuscript, this edition of A Voice From the South is both modern and readable.
Keywords: 1800-1899; afro-féminisme; amériques; approches et analyses; capitalisme; droits des femmes*; féminismes noirs; histoire et politique; militance; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; éducation; états-unis

Epistemic Injustice and Illness - Kidd, Ian James; Carel, Havi (Journal of Applied Philosophy, 2017)
This article analyses the phenomenon of epistemic injustice within contemporary healthcare. We begin by detailing the persistent complaints patients make about their testimonial frustration and hermeneutical marginalization, and the negative impact this has on their care. We offer an epistemic analysis of this problem using Miranda Fricker’s account of epistemic injustice. We detail two types of epistemic injustice, testimonial and hermeneutical, and identify the negative stereotypes and structural features of modern healthcare practices that generate them. We claim that these stereotypes and structural features render ill persons especially vulnerable to these two types of epistemic injustice. We end by proposing five avenues for further work on epistemic injustice in healthcare.
Keywords: amériques; approches et analyses; capacitisme; capitalisme; care; corps; cours; cycles supérieurs; discipline; europe; fem9000; injustices herméneutiques; injustices testimoniales; injustices épistémiques; philosophie; racisme; royaume-uni; régions géographiques; santé; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

La portée réparatrice et réconciliatrice de la Commission de vérité et réconciliation du Canada - Jaccoud, Mylène (Recherches amérindiennes au Québec, 2016)
Cet article examine les potentialités réparatrices et réconciliatrices de la Commission de vérité et réconciliation (CVR) qui a été mise en place au Canada de 2008 à 2015 en réponse aux traumatismes vécus par les autochtones dans les pensionnats. L’auteure conclut que ces potentialités sont relativement limitées. Les principales limites tiennent à l’absence d’un espace de dialogue entre les victimes et les responsables, à une centration sur les narratifs traumatiques des victimes mais aussi à une conception dépolitisée du principe de la réconciliation. La CVR du Canada n’a pas inscrit la décolonisation comme vecteur de réconciliation mais a préféré s’engager dans la voie d’une pacification des relations entre les peuples. Or, l’auteure soutient que la réconciliation entre les peuples autochtones et l’État nécessite de dépasser les gestes de guérison et de réparation matérielle ou symbolique. La décolonisation des institutions, la redistribution des territoires et une réforme constitutionnelle en profondeur restent les seules avenues possibles pour parvenir à réconcilier avec ses oppresseurs un peuple victime d’un génocide culturel.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; canada; capitalisme; commission de vérité et réconciliation; cours; criminologie; discipline; droits des personnes autochtones; féminisme décolonial; histoire et politique; justice réparatrice; justice sociale; peuples autochtones; pol4102; premier cycle; périodes historiques; racisme; réconciliation; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences

Les mesures d'austérité et les femmes: analyse des documents budgétaires depuis novembre 2008 - Couturier, Eve-Lyne; Tremblay-Pépin, Simon; Institut de recherche et informations socio-économiques (Rapport de recherche / IRIS, 2015)
Contrairement à ce que défend le gouvernement du Québec, celui-ci mène actuellement des politiques d'austérité. Ces politiques ont croisé un certain nombre de mesures de relance que le Québec a tenté d'établir depuis la crise de 2008, mais il n'en demeure pas moins que les compressions ont été plus importantes que les investissements. Cette étude montre que si les mesures de relance ont d'abord favorisé les hommes, les mesures d'austérité, quant à elles, ont surtout affecté les femmes. Ces dernières se trouvent donc doublement perdantes vis-à-vis des mesures instaurées par le gouvernement québécois depuis la crise. Si elle diffère en termes de degré, cette situation correspond à celle qu'on a pu observer en Europe lors de la mise en place de mesures d'austérité.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; austérité; canada; capitalisme; cours; discipline; histoire et politique; inégalités; patriarcat; pol4102; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; sexisme; sofia; systèmes d'oppressions; thématiques; travail; violences

Real queer?: sexual orientation and gender identity refugees in the Canadian refugee apparatus - Murray, David A. B. (Rowman & Littlefield International, Ltd., 2015)
An ethnographic exploration of sexual orientation and gender identity (SOGI) refugee claimants' experiences of navigating the complex discourses, protocols, practices and personnel of Canada's refugee determination system. "How do I prove I'm gay?" This is the central question for many refugee claimants who are claiming asylum on the basis of sexual orientation persecution. But what are the inherent challenges in obtaining this proof? How is the system that assesses this predicated upon homonormative frameworks and nervous borders? What is the impact of gender, race and class? What is an `authentic' sexual or gender identity and how can it be performed? Real Queer? is an ethnographic examination of the Canadian refugee apparatus analysing the social, cultural, political and affective dimensions of a legal and bureaucratic process predicated on separating the `authentic' from the `bogus' LGBT refugee. Through interviews, conversations and participant observation with various participants ranging from refugee claimants to their lawyers, Refugee Protection Division staff and local support group workers, it reveals the ways in which sexuality simultaneously disrupts and is folded into the nation-state's dynamic modes of gate-keeping, citizenship and identity-making, and the uneven effects of these discourses and practices on this category of transnational migrants
Keywords: 2000 à aujourd'hui; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; cours; histoire et politique; intersectionnalité; justice sociale; migration; migrations queer; premier cycle; périodes historiques; queer; régions géographiques; sex2283; système colonial; systèmes d'oppressions; thématiques

La prison est-elle obsolète ? - Davis, Angela; Peronny, Nathalie (Au diable vauvert, 2014)
"Comment et pourquoi plus de deux millions d’américains sont aujourd’hui derrière les barreaux ? Comment les entreprises font-elles profit du système carcéral ? Quels sont les mécanismes qui conduisent à criminaliser les communautés de couleur et à désaffilier politiquement de larges franges d’électeurs dans les minorités ? Comment et pourquoi plus de deux millions d'américains vivent en prison ? Comment les entreprises font-elles profit du système carcéral ? Quels sont les mécanismes qui criminalisent les communautés de couleur et désaffilient politiquement les électeurs des minorités ?
Keywords: afro-féminisme; amérique du nord; amériques; antiracisme; approches et analyses; capitalisme; cours; discipline; droits civiques; esclavagisme; féminismes noirs; histoire et politique; inégalités; justice sociale; militance; pol4212; premier cycle; racisme; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences; états-unis

“It Happened More Than Once”: Freezing Deaths in Saskatchewan - Razack, Sherene (Canadian Journal of Women and the Law, 2014)
Le présent article analyse les enquêtes et une commission sur des décès par hypothermie en Saskatchewan, au Canada. Il souligne les économies raciales et d’espace liées à ces décès, et il suggère que les relations structurelles propres au colonialisme de peuplement produisent et encouragent les expulsions continues et quotidiennes d’autochtones de la part des colonisateurs, expulsions qui sont inévitablement violentes. La ville coloniale appartient au colonisateur et son occupation est inévitablement récusée par la présence des autochtones dans la ville. L’autochtonité met mal à l’aise, car elle conteste la prétention du colonisateur à la légitimité en remettant en cause une fiction très tenace dans les états coloniaux selon laquelle les peuples autochtones seraient à l’agonie. La pratique qui consiste à repousser les autochtones aux périphéries de la ville vient du besoin des colonisateurs de maintenir les lignes de force des villes coloniales. Aujourd’hui, quand cette pratique est scrutée par le droit, comme ce fut le cas dans l’enquête sur le décès de Neil Stonechild, et dans des enquêtes sur les décès par hypothermie, elle est considérée soit comme le fait de quelques policiers sans vergogne ou encore on la nie carrément. Ce qui demeure dans les registres judiciaires, toutefois, ce sont les économies raciales d’espace dans la ville coloniale et la dévalorisation persistante de la vie autochtone, une dévalorisation que la loi produit et soutient. Dans la première partie, je présente des idées sur les économies raciales et d’espace de la ville coloniale. Dans la deuxième partie, j’étudie le cas du décès de Neil Stonechild, ainsi que la réponse du droit à ce décès, la Commission d’enquête Wright. Dans la troisième partie, j’analyse les enquêtes sur les décès par hypothermie de Rodney Niastus et de Lawrence Wegner, deux jeunes autochtones morts dix ans après Stonechild, et j’explore deux mouvements dans l’espace et le temps : Niastus et Wegner traversant la ville pour trouver la mort dans un champ gelé de la zone nord-ouest, et le cheminement que l’enquête nous invite à faire en nous faisant croire que Niastus et Wegner sont les seuls responsables de leur décès. Dans le panorama des décès d’autochtones en détention en Saskatchewan, y compris en prison, par suicide et à la suite de violents affrontements avec la police, le corps d’un autochtone est un corps qui ne peut être assassiné.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; capitalisme; cours; discipline; droit; histoire et politique; hypothermie; justice sociale; meurtre; mort; personnes autochtones; pol4105; premier cycle; périodes historiques; racisme; régions géographiques; saskatchewan; science politique et droit; sciences de l'éducation; système colonial; systèmes d'oppressions; thématiques; violences

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques

Néo-« développementisme » extractiviste, gouvernements et mouvements sociaux en Amérique latine - Svampa, Maristella (Problèmes d'Amérique latine, 2011)
La situation actuelle en Amérique latine devient contrastée et dérangeante. Elle illustre non seulement le lien persistant entre l’extractivisme néo-« développementiste » et le néolibéralisme, comme au Pérou, en Colombie ou au Mexique, mais aussi entre ce même extractivisme et les gouvernements progressistes dans un contexte de remontée en puissance de l’interventionnisme de l’État. À cette réalité, il faut ajouter la complexité d’une problématique marquée par le caractère multifactoriel des conflits où se mêlent politiques publiques et logiques d’action et de territoire diverses. Pour traiter ces différents aspects, nous mènerons notre analyse en plusieurs temps. Nous nous intéresserons tout d’abord à la pénétration de l’extractivisme dans la région pour décrire, ensuite, quelques avatars de la notion actuelle de développement. Puis, nous nous arrêterons sur les images et les idées élaborées autour de la nature américaine pour rendre compte de la permanence d’un certain imaginaire, en fonction des « avantages comparatifs » dont la région possède aujourd’hui l’usufruit. Dans les deux dernières parties, nous aborderons la question de la nouvelle cartographie des conflits suscités par la mobilisation autour de questions environnementales animée par des organisations indigènes et paysannes ainsi que par les nouveaux mouvements socio-environnementaux. Un de nos objectifs est d’illustrer les caractéristiques actuelles du tournant éco-territorial où viennent converger discours écologiste et matrice indigène et paysanne.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amérique latine; amériques; approches et analyses; capitalisme; com5170; cours; discipline; environnement; extractivisme; militance; premier cycle; périodes historiques; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques

Je suis encore sauvage ! ! ! - Vollant, Mali-Jane (Recherches amérindiennes au Québec, 2011)
Texte personnel décrivant les relations d'une famille autochtone à ma terre et leur combat contre un projet d'exploitation minière sur leur territoire.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; capitalisme; cours; environnement; exploitation minière; histoire et politique; justice sociale; militance; pol4105; premier cycle; périodes historiques; québec; régions géographiques; système colonial; systèmes d'oppressions; territoire; thématiques; uashat–mani-utenam; violences; écologie

Realizing the UN Declaration on the Rights of Indigenous Peoples: triumph, hope, and action - Joffe, Paul; Hartley, Jackie; Preston, Jennifer (Purich Pub., 2010)
Adopted by the UN General Assembly on 13 September 2007, the United Nations Declaration on the Rights of Indigenous Peoples affirms the “minimum standards for the survival, dignity and well-being of the indigenous peoples of the world.” The Declaration responds to past and ongoing injustices suffered by Indigenous peoples worldwide. It provides a strong foundation for improved relationships with states, and for the full recognition of the inherent rights of Indigenous peoples. Despite this, Canada was one of the few countries to oppose the Declaration. The contributors to this collection analyze the development of the Declaration, recall the triumph of its adoption, and illustrate the hopes and actions for its implementation. The discussion moves beyond Canadian borders to the international stage, providing accessible information and guidance on the Declaration and how it can be used to advance human rights. Policy makers, Indigenous communities, politicians, academics, lawyers, human rights advocates, NGOs, and anyone interested in the significance of the Declaration will find this to be a valuable resource. Contributors include Indigenous leaders, legal scholars and practitioners, state representatives, and representatives from NGOs, with extensive knowledge of and experience in Indigenous peoples’ human rights law, policy, and practice.
Keywords: 2000 à aujourd'hui; 2000-2009; ONU; amériques; approches et analyses; canada; capitalisme; cours; discipline; droit; droits des personnes autochtones; histoire et politique; justice sociale; pol4105; premier cycle; premiers peuples; premières nations; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; violences